SIKAP PETANI TERHADAP PROFESI PETANI: UPAYA UNTUK MEMAHAMI PETANI MELALUI PENDEKATAN PSIKOLOGI SOSIAL (KASUS PETANI DI KECAMATAN PAUH, KOTA PADANG) - Astuti, Nuraini Budi (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2016)
The farmer behaviour is influenced by many factors and one of them is what the farmer's attitude toward his profession. In order to understand the farmer's behaviour, we have to understand the farmer's attitude in advance. The purposes of this study are: 1) to analyze the farmer's attitude toward his profession, 2) to describe the schematic attitute. The data for this study were analized quantitatively using likest scale and qualitatively using theories of social psicology. The finding shows that the farmers tend to have a positive attitude. Meanwhile the schematic attitude shows that the farmers attitude toward their professions was positive and negative. therefore, extension acctivities should emphasize on changing the aspect of negative attitude.